Macro/micro fracture and failure mechanism of high borosilicate glass under dynamic compressive loading - Yubo Gao; Huying Deng; Dongwei Shu; Youqi Huang; Aoxiang Huang (Journal of Materials Research and Technology, 2025)
In this study, the dynamic mechanical properties, damage and failure mechanisms of high borosilicate glass were investigated from macro to micro perspectives through experiments, simulations and theoretical analysis. The results indicate a notable enhancement in the strength of high borosilicate glass with rising strain rates, accompanied by a gradual decline in failure strain. Due to the inertia effects and micro-scale deformation mechanisms, the strain rate dependency coefficient of glass exhibits a significantly lower strain rate dependency coefficient compared to typical crystalline materials. As the strain rate increases, there is a gradual increase in the total number of fractured particles, accompanied by a decrease in the average diameter. The DID model, which considers both the strain rate and the initial crack distribution, provides a better prediction of particle size. Upon examining cross-sections of particles, it is evident that most fractures are flat and smooth, exhibiting river-like texture and transverse fine heckle lines. The rise in the occurrence of irregular bulges and heckle lines enhances the energy absorption of the material, resulting in a strain rate effect on strength at the macroscopic level. This fundamental distinction sets high borosilicate glass apart from typical crystalline materials.